Heparanase Loosens E-Cadherin-Mediated Cell-Cell Contact via Activation of Src - Cohen-Kaplan, Victoria; Ilan, Neta; Vlodavsky, Israel (Frontiers in Oncology, 2020)
Activity of heparanase responsible for cleavage of heparan sulfate (HS) is strongly implicated in tumor metastasis. This is due primarily to remodeling of the extracellular matrix (ECM) that becomes more prone to invasion by metastatic tumor cells. In addition, heparanase promotes the development of blood and lymph vessels that mobilize disseminated cells to distant organs. Here, we provide evidence for additional mechanism by which heparanase affects cell motility, namely destruction of E-cadherin based adherent junctions (AJ). We found that overexpression of heparanase or its exogenous addition results in reduced E-cadherin levels in the cell membrane. This was associated with a substantial increase in the phosphorylation levels of E-cadherin, β-catenin, and p120-catenin, the latter recognized as a substrate of Src. Indeed, we found that Src phosphorylation is increased in heparanase overexpressing cells, associating with a marked decrease in the interaction of E-cadherin with β-catenin, which is instrumental for AJ integrity and cell-cell adhesion. Notably, the association of E-cadherin with β-catenin in heparanase overexpressing cells was restored by Src inhibitor, along with reduced cell migration. These results imply that heparanase promotes tumor metastasis by virtue of its enzymatic activity responsible for remodeling of the ECM, and by signaling aspects that result in Src-mediated phosphorylation of E-cadherin/catenins and loosening of cell-cell contacts that are required for maintaining the integrity of epithelial sheets.